BILIMLENDIRIWDI GLOBALLASTÍRÍWDA PEDAGOG IMIDJIN TRANSFORMACIYALAW - Bekimbetova, G.R. (SCIENCE and SOCIETY, 2025)
This article analyzes the image of a teacher in the education system and its role in the context of socio-economic development. The teacher's appearance, clothing culture, speech patterns, facial expressions, and pantomime are aimed at aesthetic and educational impact on students. The article also reveals the rules for creating a teacher's professional image, its goals, and ways to effectively influence students.